A review of data management and protocols for vehicular networks. (2017) - Cui, Baojiang; Yan, Xiaodan
In recent years, with the development of vehicular technology, vehicular communication has increasingly become a crucial and rising area. Creating an accident-free environment is the foremost goal of taking a real interest in this new research field. Some progress has been made in this area, new architectures, protocols and implementations of Vehicular Ad Hoc Network (VANET) have been made to supply Intelligent Transportation Services (ITS). The vehicle-to-vehicle communications play a vital role in vehicular networks, so we present a comprehensive overview of data management in this paper in order to explore the present research status with its main problems in vehicular communication. We describe the protocol of vehicular networks and the various types of data managed in that environment, also we analyse the challenges we face right now.